Effectiveness of oral versus parenteral antibiotics in cesarean section: an observational study - Bharadwaj, Malini; Momaya, Rani R.; Kaushal, Rituja (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Women undergoing caesarean section are associated with high rates of post-operative infections, which causes significant rise in infectious morbidity, duration of hospital stay and cost treatment. Implementation of appropriate antibiotic prophylaxis is desirable to prevent these complications. We aimed to observe the outcome of Intravenous single dose antibiotic prophylaxis pre-operatively followed by oral antibiotics post-operatively, in comparison to other group with multiple dose Intravenous antibiotic prophylaxis post-operatively. Methods: An observational study conducted in the department of obstetrics and gynaecology, L.N.M.C and J.K. Hospital, Kolar Road, Bhopal, on patients undergoing Elective or Emergency Lower segment caesarean section (LSCS) for a period of 6 months, on 100 subjects, with 50 participants in each group. Null hypothesis was invalidated by statistically analysing the data using chi square test, Unpaired t-test and odds ratio. Results: Prevalence of c-section was more in 25-31year age group. Abnormal presentation was the most common indication for elective LSCS in both the groups (8%), non-progress of labour and foetal distress was the most common indication for emergency LSCS in group A and B respectively (10%). There was statistically insignificant difference in the occurrence of post-operative complications in both the groups (chi sq. value=0.4285, p value=0.5127) with overall, most common complication was febrile morbidity (8% vs.12%). Significant difference noted in total bed occupancy days (unpaired t-test 1.9844) (p-value.0.000000049<0.05%). Conclusions: We recommend the use of cost-effective single dose antibiotic prophylaxis in prevention of post-operative infectious morbidity in women undergoing caesarean section.